2020
DOI: 10.1126/sciadv.aba4353
|View full text |Cite
|
Sign up to set email alerts
|

Synoviocyte-targeted therapy synergizes with TNF inhibition in arthritis reversal

Abstract: Fibroblast-like synoviocytes (FLS) are joint-lining cells that promote rheumatoid arthritis (RA) pathology. Current disease-modifying antirheumatic agents (DMARDs) operate through systemic immunosuppression. FLS-targeted approaches could potentially be combined with DMARDs to improve control of RA without increasing immunosuppression. Here, we assessed the potential of immunoglobulin-like domains 1 and 2 (Ig1&2), a decoy protein that activates the receptor tyrosine phosphatase sigma (PTPRS) on FLS, for RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…However, healthy individuals do not undergo therapeutic joint surgery, it is therefore difficult to obtain healthy FLS. As control FLS, we and others [ 39 , 40 , 41 ] therefore use FLS from patients with osteoarthritis (OA) which are less aggressive than RA-FLS in terms of migration, invasiveness, and production of cytokine, chemokines and growth factors [ 42 , 43 ]. Concentrations of 10 μg/mL PEG-HCCs and higher induce the death of both RA-FLS and OA-FLS ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…However, healthy individuals do not undergo therapeutic joint surgery, it is therefore difficult to obtain healthy FLS. As control FLS, we and others [ 39 , 40 , 41 ] therefore use FLS from patients with osteoarthritis (OA) which are less aggressive than RA-FLS in terms of migration, invasiveness, and production of cytokine, chemokines and growth factors [ 42 , 43 ]. Concentrations of 10 μg/mL PEG-HCCs and higher induce the death of both RA-FLS and OA-FLS ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…Other agents have been reported to reduce inflammation in models of arthritis that are insufficient alone, but utilize a complementary pathway that favorably modulates the activity of a known therapeutic agent. For example, the receptor tyrosine phosphatase sigma (PTPRS) activating decoy protein attenuated severity of arthritis when combined with low dose of a TNF inhibitor ( Svensson et al, 2020 ), but was insufficient in itself to have an effect. In addition, we have reported that the combination of an inhibitor of cell proliferation and a TNF inhibitor exerted synergistic effects without reducing immune responses ( Hosoya et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCL11, CCR3, and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) primers were purchased from Qiagen. Quantitative PCR was performed using SYBR Green quantitative PCR master mix (Qiagen) on a C1000 thermal cycler (Bio Rad, Hercules, CA, USA) as described previously 5 . The efficiency of the primer assays was guaranteed by the manufacturer to be > 90%.…”
Section: Methodsmentioning
confidence: 99%
“…RA FLS also contribute to the inflammation through the secretion of cytokines and chemokines which induce and maintain the inflammatory cells, including infiltrating lymphocytes and monocytes. It has been suggested that combination of agents selectively targeting RA FLS and current disease-modifying anti-rheumatic drugs is an option for therapy to improve disease control without increasing the risk of infection 3 5 .…”
Section: Introductionmentioning
confidence: 99%